Hubungan Penguasaan Syarat-Syarat Paragraf Dengan Kemampuan Menulis Karangan Naras Pada Siswa Kelas X Sma Negeri 1 Batangtoru - Agus Salim Batubara (Institute of Information Technology and Social Science (IITSS), 2020)
The purpose of this study was to determine whether there is a significant relationship between effective paragraph mastery and the ability to write narrative essays on Class X students of SMA Negeri 1 Batang Toru. The description method was used in conducting this research. The population of this study was all 120 Class X students of SMA Negeri 1 Batang Toru. The research sample was taken using a random sampling technique, which is 25% of the population. So, the sample of this study ranges from 30 students. Then the authors provide the test as a data collection technique. In data analysis, the authors use descriptive analysis techniques and statistical analysis techniques using the Product Moment r formula by Pearson. Descriptive analysis results show that Class X students of SMA Negeri 1 Batang Toru gained 72.16 (good category) in writing narrative essays. Meanwhile students get an average score of 67.00 (enough categories) in effective paragraph mastery. The results of statistical analysis show that the rxy value is greater than the rtablevalue (0.974 > 0.374). Thus, it can be said that the hypothesis in this study can be accepted. This means that there is a significant relationship between the mastery of paragraph requirements and the ability to write narrative essays on Class X students of SMA Negeri 1 Batang Toru.